-6(8x-4)+3x=2

Simple and best practice solution for -6(8x-4)+3x=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(8x-4)+3x=2 equation:



-6(8x-4)+3x=2
We move all terms to the left:
-6(8x-4)+3x-(2)=0
We add all the numbers together, and all the variables
3x-6(8x-4)-2=0
We multiply parentheses
3x-48x+24-2=0
We add all the numbers together, and all the variables
-45x+22=0
We move all terms containing x to the left, all other terms to the right
-45x=-22
x=-22/-45
x=22/45

See similar equations:

| 3/4x-9=0 | | 5x-12=3-x | | 12+n=14 | | 6x+5-12x=7x+9-19x | | 6-2(8x-8)=1 | | 2(2y-5)+y=7-2+2y | | 5=0.5p | | -4m-16=4(1+2m)+8 | | 5-y=2+4y | | 2x-4÷2=6x+3 | | y-15.4=15.2 | | T=-4t^2+14t-6 | | 3x-9-6=4x+4 | | 6c-26=8c | | -3(x-1)=2(2-3x)+1 | | g/72-3/9=3/9 | | 50(3x)=2 | | 3e=3|4 | | z÷9=1.6 | | 15-4x=4(3-x)+2 | | 5(x+1)^1/4=10 | | 7/5=-4/5x | | 16(x+19)=23(x−19) | | 3(50x)=2 | | m-(-14)=-11 | | 27x=-6 | | 3z-11=7 | | 2/5(15x-10)=26 | | 11(x-2)=6(x-3)11 | | 5x-(3x+7)=83 | | 5b+9=-b-3 | | 3z/10-2=9 |

Equations solver categories